Pemanfaatan Abu Terbang (Fly Ash) Batu Bara sebagai Campuran Pembuatan Bata Beton - Haspiadi Haspiadi (Balai Riset dan Standardisasi Industri Samarinda, 2016)
The use of coal sources of energy has produce fly ashes, which has became a big source of pollution. Fly ash is a fine glass like powder recovered from gases created by coal fired electrical power generation. One of the alternatives to solve this problem is by using this material to produce paving block. This research was conducted to find possible use of fly ash to replace sand in paving block. In this research the effect of replacing zero to 40 % sand with fly ash is evaluated. It is found out that best result could be obtained by replacing sand by 10 % fly ash which meet the requirement according to National Standard of Indonesia SNI 03-0691-1996 Paving Block. The results of compression strength and surface area indicate that the requirement for parking area application (class B). On the other hand the result of water absorption analysis Indicate the requirements of standard for garden place where garden plants. tools, etc are sold and other specification with the same level (class C).